The effects of sodium chloride in the ultimate tensile strength of nitinol wires - Lim, Dennis C.
Twenty-four samples from each company (AVM - Ormoc and Ahescor - Unitek) were used in the study. The nitinol wires were divided according to their respective companies for the following groupings: one month, two months and three months. One half of the total length of wire were removed, coded and stored at an incubator with a maintaining temperature of 37 degree celsius (control group), while the rest of the wires were also coded and immersed in a 1sodium chloride solution and stored in the same incubator (experimental group). After a month of immersion, 8 wires from each company were removed from the container (control and experimental). One-half inch test span from each wire were then cut and subjected to Scanning Electron Microscope, to check for corrosion, while the rest of the wire were subjected to Riehl Testing Machine for the Ultimate Tensile Strength of the wire. The procedure is repeated for three months with one month interval. No statistical difference between the experimental and control group for the time interval was seen at an alpha level of significance of 0.10. While for the Scanning Electron Microscope examination, only scratches due to manufacturing defects were found on the surfaces of the wires; except for the 3rd month, wherein sodium chloride crystals were observed. However, no sign of corrosion was seen on the surface of the wires.